Non-invasive applications of Raman spectroscopy in assisted reproduction - Sui, Mingxing; Si, Lihui; Chen, Zhuoyue; Lu, Yingli; Li, Hongru (Frontiers in Endocrinology, 2025)
This review explores the non-invasive applications of Raman spectroscopy in assisted reproductive technology (ART). Raman spectroscopy, a powerful tool for analyzing biological samples, has shown great potential in enhancing ART outcomes through various applications such as sperm quality assessment, oocyte evaluation, and embryo selection. The non-destructive nature and high specificity of this technique enable detailed biochemical analysis at the cellular level, offering valuable insights into cellular processes without harming for the samples. The review highlights recent advancements and studies demonstrating the efficacy of Raman spectroscopy in improving the selection criteria for gametes and embryos, ultimately contributing to higher success rates in ART. Future perspectives on integrating Raman spectroscopy with other technologies to further enhance its applicability in reproductive medicine are also discussed.